2019
DOI: 10.1002/ird.2362
|View full text |Cite
|
Sign up to set email alerts
|

Optimization of the Cropping Pattern of Main Cereals and Improving Water Productivity: Application of the Water Footprint Concept

Abstract: Different components of water footprint (WF) (green, blue, grey and white) and WF volume (WFV) were estimated for three main cereal crops in Iran (wheat, barley and maize) in the main cereal‐producing provinces. In order to classify the selected provinces according to their corresponding WFVs, hierarchical cluster analysis (HCA) was applied for clustering the WFV of maize, barley and wheat in irrigated and rainfed conditions. Then, the linear programming (LP) technique was used to determine the optimal cultiva… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

0
3
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 13 publications
(3 citation statements)
references
References 33 publications
0
3
0
Order By: Relevance
“…The results showed that the current agricultural system has caused 206% of water scarcity in South Khorasan province. Ramezani Etedali et al 37 studied the optimal cropping pattern of main cereals (wheat, barley, and corn) in 15 provinces of Iran with linear programming. Their goal was to obtain an optimal cropping pattern based on the minimum virtual water of crops.…”
Section: Introductionmentioning
confidence: 99%
“…The results showed that the current agricultural system has caused 206% of water scarcity in South Khorasan province. Ramezani Etedali et al 37 studied the optimal cropping pattern of main cereals (wheat, barley, and corn) in 15 provinces of Iran with linear programming. Their goal was to obtain an optimal cropping pattern based on the minimum virtual water of crops.…”
Section: Introductionmentioning
confidence: 99%
“…They reported improvement in net financial return by 92.5% and increase in cropped area by 109.7% under deficit irrigation. Etedali et al (2019) employed the linear programming technique to compute the optimal cultivated area for cereals in order to maximize the total national water footprint volume in irrigated and rainfed lands.…”
Section: Introductionmentioning
confidence: 99%
“…Although there are a few studies investigates the uncertainty of parameters with grey data or grey numbers in machine scheduling problems, there are lots of examples about mathematical programming with grey numbers for other problems such as reservoir watershed planning (Chang et al, 1996), water quality management (Huang, 1996;Karmakar and Mujumdar, 2006), project selection (Amirian and Sahraeian, 2018), waste management planning (Huang et al, 1994(Huang et al, , 1995a, game theory (Kose and Forrest, 2015), irrigation planning (Ramezani Etedali et al, 2019), resource allocation (Chalvatzis et al, 2019), electricity generation planning (Malekpoor et al, 2018), economy management (Wang, 2017) and assembly line balancing (Arık et al, 2019). These examples are diversified.…”
Section: Introductionmentioning
confidence: 99%